Graphite fabric reinforced PAEK composites by novel impregnation-co-film technique. (26th May 2020) - Marathe, Umesh; Padhan, Meghashree; Bijwe, Jayashree
Abstract: High performance polymers such as Poly(ether ether ketone) (PEEK), Poly(aryl ether ketone) (PAEK), Poly(ether ketone ketone) (PEKK), etc exhibit high melting points, 343 °C, 373 °C and 338 °C respectively and very high melt viscosity. They do not have appropriate solvents, which could open the ways to process their fabric reinforced composites; by impregnation technique followed by compression molding. Film stacking and powder sprinkling are the only possible techniques, which lead to weak crossover points due to non-wetting by the resin and finally resulting in inferior mechanical and interfacial properties and high amount of voids. In order to solve these problems, a novel technique called impregnation-co-film (ICF) is explored in this work. Polyetherimide (PEI) (10 wt% in dichloromethane solution) pre-impregnated graphite fabric prepregs were used before applying film technique followed by compression molding. The study compares properties such as density, void content, flexural strength, impact strength, Interlaminar shear strength (ILSS), thermal stability (in air) and interface by field emission scanning electron microscopy for the composite prepared with film stacking technique and that by impregnation-co-film stacking technique. It was confirmed that the new ICF technique proved to be significantly promising than the older technique almost in all aspects with 120% improvement in ILSS, 127% in flexural strength and 200% decrease in void content.